Topsy+Tim go to the zoo - Adamson, Jean; Adamson, Gareth (Loughborough, Ladybird, 1998)
Topsy and Tim books are divided into five themes: school; going out; special friends; first experiences; and people who help us. They present fun, factual stories dealing with new experiences and storylines suited to "read to" and older "self read" situations.